Indonesian Syariah : Defining a National School of Islamic Law - Hooker, M. B. (Book collections on Project MUSE., 2008)
The creation of a national school of Islamic law in Indonesia has been on the legal agenda for the past fifty years. This book is a summary of what has been achieved. The material shows us a complex range of references for syariah. These include the formal structures of a "new fiqh", philosophies of law, transmissions of syariah through tertiary curricula and the Friday sermon in mosques, a bureaucratic form for conducting the Hajj, and contemporary debates on syariah values as expressions of ...